Current interest in the theory of organizational path dependence: A short update on the occasion of the 2019 AMR Decade Award - Jörg Sydow; Georg Schreyögg; Jochen Koch (Freie Universität Berlin, School of Business & Economics, 2020)
This discussion paper reports and reflects on the reception of our article "Organizational path dependence: Opening the black box", which was published in 2009 in the Academy of Management Review and granted the AMR Decade Award in 2019. While we were invited by the editor of the journal to discuss the criticism evoked by that paper, to re-examine our original propositions in the light of advanced insights and to outline new avenues for future research on organizational path dependence, in this discussion paper we report in some detail and comment on the citation landscape of our original AMR piece.
urn:nbn:de:kobv:188-refubium-28096-5
Keywords: 650; Management; Organization; Strategy; Structural Inertia; Institutional Persistence; Path Dependence; Path Creation; History